Phylogenetic and seasonal patterns in the microbiome of mosquito vectors - Klein, Amelie (Jihočeská univerzita, 2020)
The aim of this thesis was to identify phylogenetic and seasonal patterns in mosquitoes' microbiome. Thereby, the season around summer was targeted and the species Culex pipiens with the two forms pipiens and molestus as well as their hybrid form were of interest. For the microbiome analysis, the 16s rRNA gene was targeted in individual samples.
Phylogenetic and seasonal patterns in the microbiome of mosquito vectors
Keywords: mosquito; Culex; 16s rRNA gene; microbiome; pipiens; molestus; hybrid; season; Wolbachia; mosquito; Culex; 16s rRNA gene; microbiome; pipiens; molestus; hybrid; season; Wolbachia